From Stalingrad to Grozny: Patriotism, political pressure, and literature in the war reporting of Vassily Grossman and Anna Politkovskaya. (April 2014) - Rodgers, James
Comparing the work of the 20th-century Soviet journalist and writer, Vassily Grossman, with that of his compatriot, Anna Politkovskaya, almost half a century later, this article examines the two journalists' writing for what it tells us about the changing nature of Russian journalism, and reporter involvement in the coverage of war. Grossman was reporting on his country's fight for survival in a war with Nazi Germany; Politkovskaya had no peer in her coverage of the bloodiest consequence of the collapse of that country, the Soviet Union: the wars in Chechnya. It also considers the literary nature of Grossman and Politkovskaya's reporting. The article argues that the two journalists' work has significance far beyond the time when they were reporting, and should therefore be more widely read and studied for what it tells us about covering conflict, and especially civilian suffering and, in the case of Politkovskaya, counter-insurgency.